2016
DOI: 10.1016/j.celrep.2015.12.101
|View full text |Cite
|
Sign up to set email alerts
|

Nac1 Coordinates a Sub-network of Pluripotency Factors to Regulate Embryonic Stem Cell Differentiation

Abstract: Pluripotent cells give rise to distinct cell types during development and are regulated by often self-reinforcing molecular networks. How such networks allow cells to differentiate is less well understood. Here, we use integrative methods to show that external signals induce reorganization of the mouse embryonic stem cell pluripotency network and that a sub-network of four factors - Nac1, Oct4, Tcf3 and Sox2 – regulates their differentiation into the alternative mesendodermal and neuroectodermal fates. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
(94 reference statements)
2
36
0
Order By: Relevance
“…7a, b). The ability of RA to drive ectodermal differentiation seemed unaffected under these conditions, as reported before 25 .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…7a, b). The ability of RA to drive ectodermal differentiation seemed unaffected under these conditions, as reported before 25 .…”
Section: Resultssupporting
confidence: 60%
“…Importantly, the two factors we studied in detail, Gbx2 and Tbx3, were previously determined to be part of an essential pluripotency network [51][52][53][54][55] . It has been suggested before that some pluripotency genes are also involved in lineage specification 25,48,49 . Thomson et al showed that Sox2 and Oct4 promote the neuroectodermal and mesendodermal lineage, respectively 48 .…”
Section: Discussionmentioning
confidence: 99%
“…NAC1 has been reported to have a role in regulating the stemness and differentiation of stem cells through its interaction with the factors like Nanog, Oct4, Tcf3 and Sox2. 6 , 37 , 38 As altered energy metabolism can impact fate of stem cells, 39 the NAC1-promoted glycolysis may contribute to its role in regulating differentiation of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Nac1 was reported to be needed for ME differentiation of ESCs. Nac1 KD resulted in a significant reduction of the ME fate, but induced the NE fate choice [ 33 ]. However, our study indicates that Nac1 KD facilitates the ME differentiation of ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Nac1 knockdown (KD) induces ESC differentiation [ 31 ], whereas Nac1 knockout does not induce embryonic lethality or result in grossly noticeable morphological phenotypes in mice [ 32 ]. Following the use of integrative methodologies, Nac1 has been suggested to act as a lineage specifier that mediates mesendoderm (ME) and neuroectoderm (NE) cell fate selection [ 33 ]. However, the precise functions and mechanisms underlying the role of Nac1 in the regulation of ESC self-renewal and pluripotency are not well defined.…”
Section: Introductionmentioning
confidence: 99%